ELASTICITY OF DEMAND ON THE TWO SIDES OF THE RECTANGULAR HYPERBOLA - Mukerji, A. M. El-Beih (Dirasat in Economics and Business, 1968)
While explaining elasticity of demand most of the modern books on economics refer to the important relationships which exist among elasticity, price changes and the total amount which the consumers spend on a certain commodity. If a decrease in price raises the quan- tity so much as to increase the total outlay of the consumers, then